2015
DOI: 10.1007/s10903-015-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Depression Among Mexican Americans Living in U.S.–Mexico Border and Non-Border Areas

Abstract: Background Factors associated with CES-D depression among Mexican Americans living on and off the U.S.-Mexico border are examined. Methods Data are from two studies of Mexican American adults. The Border Survey conducted face-to-face interviews in urban U.S.-Mexico border counties of California, Arizona, New Mexico, and Texas (N=1,307). The non-border HABLAS survey conducted face-to-face interviews in Houston, Los Angeles, New York, Philadelphia, and Miami (N=1,288). Both surveys used a multistage cluster sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…Research suggests reducing tension associated with stress is one reason people use alcohol (Greeley & Oei, 1999; Park, Armeli, & Tennen, 2004), and that this relationship may differ by gender (e.g., Nolen-Hoeksema, 2004). Similar patterns have been found for certain stressors among Latina/os (e.g., Golbach, Cardoso, Cervantes, & Duan, 2015), with suggestion of distinct patterns for each gender (Vaeth, Caetano, & Mills, 2016). However, research examining the cumulative effects of general university stressors with others highly relevant to Latina/o college students (i.e., global stress) in relation to alcohol use is lacking.…”
supporting
confidence: 74%
“…Research suggests reducing tension associated with stress is one reason people use alcohol (Greeley & Oei, 1999; Park, Armeli, & Tennen, 2004), and that this relationship may differ by gender (e.g., Nolen-Hoeksema, 2004). Similar patterns have been found for certain stressors among Latina/os (e.g., Golbach, Cardoso, Cervantes, & Duan, 2015), with suggestion of distinct patterns for each gender (Vaeth, Caetano, & Mills, 2016). However, research examining the cumulative effects of general university stressors with others highly relevant to Latina/o college students (i.e., global stress) in relation to alcohol use is lacking.…”
supporting
confidence: 74%
“…Analyses of The Border Study found a prevalence of 19% among men not living on the U.S. Mexican border and 14.67% for those living on the border. Depression prevalence in women was 25% for nonborder residents and 23.16% for border residents (Vaeth et al, 2016). However, these studies included multiple occupations and, in some, data from communities in the Bronx, New York, and Chicago, Illinois (e.g., HCHS/SOL).…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms in the past week, the focal dependent variable for the current study, were assessed using the 10-item version of the CES-D scale (Grzywacz, Hovey et al, 2006; Guarnaccia, Angel, & Worobey, 1989; Kohout, Berkman, Evans, & Coroni-Huntley, 1993; Magaña & Hovey, 2003; Radloff, 1977; Sandberg et al, 2012). The CES-D was selected because it is one of the most widely used measures of depressive symptomatology in community samples and has been found to have good internal reliability and construct validity among Mexican Americans, including samples consisting of primarily low-income crop workers (Casillas et al, 2012; Grzywacz, Alterman et al, 2010; Grzywacz, Quandt et al, 2006; Kohout et al, 1993; Ortega, Rosenheck, Alegría, & Desai, 2000; Vaeth, Caetano, & Mills, 2016; Wassertheil-Smoller et al, 2014). Crop workers first were asked if they experienced a depressive symptom in the previous 7 days, and if yes, they were asked how many of the past 7 days they experienced the symptom.…”
Section: Methodsmentioning
confidence: 99%
“…Given the current political climate of 2019 and the myriad of stressors undocumented Latinx women currently face it seems logical there would be deleterious effects on their mental health. In the last decade studies have begun to focus on the psychological impact of undocumented status on the Latinx population in general, but few with Latinx women specifically (Arbona et al, 2010; Hagan et al, 2010; Vaeth, Caetano, & Mills, 2016). With the rapidly changing immigration policy, few studies have addressed the consequences of current events and the severity of the psychological impact on the lives of undocumented Latinx women (Cobb et al, 2017; Garcini et al, 2018, 2019).…”
Section: Mental Health Implicationsmentioning
confidence: 99%
“…Based on previous research, many undocumented immigrants are at greater risk for emotional distress and mental health issues (Chung, Bemak, Ortiz, & Sandoval-Perez, 2008; Cobb et al, 2017; Garcini et al, 2018, 2019; Ornelas & Perreira, 2011; Sullivan & Rehm, 2005). Vaeth et al (2016) found undocumented Latinx immigrants experienced a constant fear of deportation and this resulted in high incidents of psychiatric disorders. Of the psychiatric disorders depression and anxiety were the most common (Cobb et al, 2016; Hagan et al, 2010; Miranda et al, 2005; Ornelas & Perreira, 2011; Potochnick & Perreira, 2010).…”
Section: Mental Health Implicationsmentioning
confidence: 99%